Cellular and molecular correlates of ectopic activity in patients with atrial fibrillation - Voigt, Niels; Dobrev, Dobromir (Europace, 2012)
Abstract. Atrial fibrillation (AF) is the most frequent arrhythmia and is associated with increased morbidity and mortality. Current drugs for AF treatment hav